2016
DOI: 10.1016/j.neuropsychologia.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

From mind wandering to involuntary retrieval: Age-related differences in spontaneous cognitive processes

Abstract: The majority of studies that have investigated the effects of healthy aging on cognition have focused on age-related differences in voluntary and deliberately engaged cognitive processes. Yet many forms of cognition occur spontaneously, without any deliberate attempt at engaging them. In this article we review studies that have assessed age-related differences in four such types of spontaneous thought processes: mind-wandering, involuntary autobiographical memory, intrusive thoughts, and spontaneous prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
102
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 130 publications
(287 reference statements)
14
102
5
Order By: Relevance
“…Gyurkovics, Balota & Jackson, 2017). This novel prediction contradicts theories of cognitive aging and a large body of evidence, which shows that aging mostly disrupts more difficult tasks that rely on deliberate control processes, while performance on tasks involving spontaneous retrieval is relatively spared (Craik & Grady, 2002;Maillet & Schacter, 2016a).…”
Section: Reduced Mind-wandering In Mild Cognitive Impairment: Testingcontrasting
confidence: 64%
“…Gyurkovics, Balota & Jackson, 2017). This novel prediction contradicts theories of cognitive aging and a large body of evidence, which shows that aging mostly disrupts more difficult tasks that rely on deliberate control processes, while performance on tasks involving spontaneous retrieval is relatively spared (Craik & Grady, 2002;Maillet & Schacter, 2016a).…”
Section: Reduced Mind-wandering In Mild Cognitive Impairment: Testingcontrasting
confidence: 64%
“…Future studies should investigate these effects in other populations of special interest for research on MW, such as elderly people. Studies on aging have shown a reduction in MW in healthy older adults compared to young adults (see for a Running head: Role of verbal cues in mind wandering 22 discussion, Maillet & Schacter, 2016a), and an age-related increase in reliance on the environment (Craik, 1986;Maillet & Schacter, 2016b). Future studies should examine the effects of the exposure to task-irrelevant verbal cues on the frequency and temporal orientation of MW in elderly people and verify whether the presence of external cues might increase the frequency of engagement in MW in elderly people, to a stronger extent than in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some researchers [78] have suggested that the focus on future thoughts during mind wandering episodes suggests a possible functional role for mind-wandering in problem solving, but it is unknown whether such functionality is equally characteristic of intentional and unintentional mind-wandering. Finally, recent research on cognitive aging has also suggested a link between mind-wandering and involuntary autobiographical memory retrieval – older adults show reductions in both compared with young adults [79] – but it is unknown whether the age-related reduction in mind wandering applies to both intentional and unintentional varieties.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%